Prevalence of Group B Streptococcus Colonization in Pregnant Women - Zahra Wasim, Muhammad Imran Afsar, Syed Saddam Hussain, Tahira Riaz, Nusrat Noor, Sadaf Shafique (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the prevalence of group B streptococcus (GBS) colonization in women in 3rd trimester of pregnancy. Study Design: A cross-sectional study. Place and Duration of the Study: This study was done at The Department of Obstetrics & Gynecology, The Combined Military Hospital (CMH), Risalpur, Pakistan from 1st July 2021 to 31st December 2021. Material and Methods: We included a total of 261 pregnant women in 3rd trimester aged between 18 to 40 years irrespective of parity or gravidity status. Age, area of residence, parity status and gestational age were noted. During the vaginal examination of the pregnant women, vaginal swabs using sterilized cotton swabs were acquired from all study participants. All acquired vaginal swabs were sent to institutional pathological laboratory. Prevalence of GBS colonization was noted. Results: In a total of 261 pregnant women, mean age was 28.4±6.2 years while 178 (68.2%) women were aged between 20 to 30 years. Area of residence was rural in 162 (62.1%) women. There were 146 (55.9%) women with gestational age between 30 to 35 weeks. Majority of the women, 195 (74.7%) were multiparous. Vaginal discharge was reported in 112 (42.9%) pregnant women. Prevalence of GBS colonization was noted in 48 (18.4%) pregnant ladies. Vaginal discharges was observed to have statistically significant association with the presence of GBS colonization (p=0.0388). Conclusion: Prevalence of GBS colonization was high in pregnant ladies visiting a tertiary care hospital during 3rd trimester of pregnancy. Pregnant women with vaginal discharges were observed to have statistically significant association with the presence of GBS colonization.